The Effect of Electronic Service Quality on Customer Trust and Its Implication on Repurchase Intention of Online Travel Agency Customers - Frans Sudirjo; Asnawati; Slamet Riyadi; Musran Munizu; Wa Ode Nur Ainun (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study intends to determine how the quality of electronic services affects customer trust and how it affects e-commerce users' willingness to make additional purchases. This study approaches the topic of e-commerce research quantitatively. A sample of 100 e-commerce users' responses was used in this study. Using a questionnaire to obtain data. The findings indicated that the e-service quality variable affected consumer trust and repurchase intention to some extent. Repurchase intention is influenced by the customer trust factor. E-service quality and customer trust both influences repurchase intention simultaneously. Through consumer trust, inconsistent e-service quality has an indirect impact on customers' willingness to repurchase. More consumer data protection should be offered through e-commerce. It is advised that other variables and methodological approaches be used in future studies so that the scope and depth of study in the field of marketing can be increased